Inhibitory Effect of the LY2109761 on the Development of Human Keloid Fibroblasts. (10th February 2021) - Wang, Xiuxia; Gu, Chuan; Shang, Feng; Jin, Rui; Zhou, Jia; Gao, Zhen
Abstract : Keloids are scars characterized by abnormal proliferation of fibroblasts and overproduction of extracellular matrix components including collagen. We previously showed that LY2109761, a transforming growth factor- (TGF-) β receptor inhibitor, suppressed the secretion of matrix components and slowed the proliferation of fibroblasts derived from human hypertrophic scar tissue. However, the exact mechanism underlying this effect remains unclear. Here, we replicated the above results in keloid-derived fibroblasts and show that LY2109761 promoted apoptosis, decreased the phosphorylation of Smad2 and Smad3, and suppressed TGF- β 1. These results suggest that the development and pathogenesis of keloids are positively regulated by the Smad2/3 signaling pathway and the upregulation of TGF- β 1 receptors. LY2109761 and other inhibitors of these processes may therefore serve as therapeutic targets to limit excessive scarring after injury.